Cover Feature: The Road to Bisacyldigermanes: A New Compound Class Suitable as Visible Light Photoinitiators (ChemPhotoChem 9/2022). Issue 9 (15th September 2022) - Wiesner, Tanja; Glotz, Gabriel; Wunnicke, Odo; Bleger, David; Knezevic, Ivana; Torvisco, Ana; Fischer, Roland C.; Kelterer, Anne‐Marie; Gescheidt, Georg; Haas, Michael
Abstract : The Cover Feature illustrates the road towards the new compound class bisacyldigermanes. These derivatives are highly efficient photoinitiators (PIs) which, among others, exhibit excellent photobleaching properties. In the image, the passengers journey from their starting point (widely used acylphosphine oxides, depicted in the rear‐view mirror) and drive, with the aid of a roadmap, towards their destination, bypassing toxicity and mutagenicity to reach an oasis with the new compound class bisacyldigermanes. Cover design by Ilva Leinich. More information can be found in the Research Article by Michael Haas and co‐workers .